”By my Lords comand, I am to acquainte you”: An Edition of the Seventeenth-Century Correspondence of the Wentworth Family in the Folger Shakespeare Library - Rastas, Johanna (My University, 2016)
This thesis is an edition of the correspondence of the Yorkshirean Wentworth family. The aim of the edition is to provide these handwritten manuscripts to a wider audience by transcribing them. The material has been acquired from the Folger Shakespeare Library, and the transcriptions presented in this thesis are a part of their database called Early Modern Manuscripts Online. My material consists of fifteen documents from the early modern period which have been sent to or sent by members of the Wentworth family. Fourteen of these documents are letters, and one is a warrant written in the form of a letter. In the Folger Shakespeare Library the documents form the section 2.1. Correspondence of the Wentworth family in a larger collection called Papers of the Cavendish-Talbot family. The documents have been transcribed diplomatically in order to retain the character of the original manuscripts. In addition to the transcriptions, background chapters on letter writing, the historical and linguistic context, and palaeography are provided. Furthermore, each text includes a commentary containing a brief summary of the text and a description of the manuscript. Notes concerning specific words or concepts are also provided to make the texts easier to understand. Additionally, the transcriptions are encoded in XML for the purposes of the Folger Shakespeare Library. These earlier unedited manuscripts reassert the status of the Wentworth family in the early modern English society and provide information about letter writing conventions, language, and palaeographical conventions in early modern England. This edition can be used in further studies, for example as part of a larger corpus.